2015
DOI: 10.14529/met150406
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aluminium on electric resistivity of nickel-aluminium alloys

Abstract: Уральский федеральный университет, г. Екатеринбург Изучены температурные и концентрационные зависимости удельного электросопротивления сплавов системы «никель-алюминий» в жидком состоянии. Вид политерм ρ определяется исходным фазовым составом сплавов. Гистерезис политерм связан с устранением влияния на расплав структуры и фазового состав исходных твердых образцов и переходом системы в равновесное и однородное состояние, что способствует большему структурному упорядочению интерметаллидов. Экспериментальные данн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…As results of the experiments it has been shown that, the form of the temperature dependence of the resistivity ρ (t) is a characteristic of high-temperature alloys [1,9].…”
Section: Experiments and Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…As results of the experiments it has been shown that, the form of the temperature dependence of the resistivity ρ (t) is a characteristic of high-temperature alloys [1,9].…”
Section: Experiments and Discussionmentioning
confidence: 96%
“…Taking into account the results of studies of binary alloys [3,4], the compositions Ni + 10 and + 15 wt. % Cr each is aluminum alloyed in an amount of 5 and 10% by weight.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations